A NORMATIVE REVIEW OF THE SIMULTANEOUS GENERAL ELECTION AND REGIONAL HEAD ELECTION DELAY - Ansori, Ansori; Fahmi, Agung Ali; Mukhlish, Mukhlish (TRUNOJOYO LAW REVIEW, 2022)
A government system based on people's sovereignty can be called a democratic government system. Democracy itself is realized by a government based on representatives of the people who are democratically elected by means of general elections. General elections or elections are a logical consequence of a country that adheres to a democratic system, and democracy is a safe way to maintain control over the rule of law. article 3 of Law NO. 7 of 2017 concerning ELECTIONS states that ELECTIONS must be held based on the principles of being effective and efficient. Therefore, the separation of national elections and local elections is to represent the existence of this article. Simultaneous elections to be held in 2024, namely elections on a national and local scale, will bring various negative impacts. If the 2022 and 2023 Regional head elections are postponed and held in 2024, the Jakarta-centric issue is very dominant and local issues or agendas are sidelined. Meanwhile, the regulation related to the postponement of the Regional head election is contained in Article 201 paragraph (9), (10), and (11) of Law no. 1 of 2015 concerning Stipulation of Government Regulation into Law no. 1 of 2014 concerning the Election of Governors, Regents, and Mayors into Law.